The Construction of Canadian Identity from Abroad
XXXIII, 380 p. 22 illus., 14 illus. in color.
Keywords: “The contributors to this volume take a compelling look at Canadian identity through the lenses of Canadians living abroad. These expats have a unique perspective on being Canadian, as their identity is conditioned not only by who they are but where they are. This volume is a must-read. Each chapter provides a glimpse into that looking glass, helping us understand how we see the world, see ourselves, and understand and come to terms with our identities.” —Michael K. Hawes, President and CEO, Fulbright Canada Migration and the impact that immigrants have on Canada is and always has been central to a robust understanding of Canadian identity. However, despite claims that “the world needs more Canada,” Canadians, their governments, and scholars pay much less attention to the estimated 3 million Canadian expatriates who live elsewhere. The Construction of Canadian Identity from Abroad features Canadian scholars who live and work outside Canada (or have recently returned to Canada) and who write and think deeply about identity construction. What happens when that Canadian is a scholar whose teaching, research and scholarship, professional development, and/or community engagement focuses directly on Canada? How does being abroad affect how we interpret Canada? In short, in what ways does “externality” affect how Canadian expat scholars intellectually approach, construct, and identify with Canada? This engaging volume is ideal for university students, scholars, government officials, and the general public. Christopher Kirkey is Director of the Center for the Study of Canada and Institute on Quebec Studies at State University of New York College at Plattsburgh, USA, and serves as President of the Association for Canadian Studies in the United States (ACSUS). He is a co-editor, with Michael K. Hawes and Andrew C. Holman, of Canada in 1968: A Year and Its Legacies (2021). Richard Nimijeanis a member of the School of Indigenous and Canadian Studies at Carleton University, Ottawa, Canada, and a Visiting Professor in the Department of English and American Studies at Masaryk University in Brno, Czech Republic. He is a co-editor, with David Carment, of Canada Among Nations 2020: Political Turmoil in a Tumultuous World (2021).